Mass Spectrometry-Based Differentiation of Oral Tongue Squamous Cell Carcinoma and Nontumor Regions With the SpiderMass Technology - Ogrinc, Nina; Attencourt, Christophe; Colin, Emilien; Boudahi, Ahmed; Tebbakha, Riad; Salzet, Michel; Testelin, Sylvie; Dakpé, Stéphanie; Fournier, Isabelle (Frontiers in Oral Health, 2022)
Oral cavity cancers are the 15th most common cancer with more than 350,000 new cases and approximately 178,000 deaths each year. Among them, squamous cell carcinoma (SCC) accounts for more than 90% of tumors located in the oral cavity and on oropharynx. For the oral cavity SCC the surgical resection remains the primary course of treatment. Generally, surgical margins are defined intraoperatively using visual and tactile elements. However, in 15 to 30 percent of cases, positive margins are found after histopathological examination several days post-surgery. Technologies based on mass spectrometry (MS) have recently been developed to help guide surgical resection. The SpiderMass technology is designed for in vivo real-time analysis under minimally invasive conditions. This instrument achieves tissue micro-sampling and real-time molecular analysis with the combination of a laser microprobe and a mass spectrometer. It ultimately acts as a tool to support histopathological decision-making and diagnosis. The pilot study included 14 patients treated for tongue SCC (T1 to T4) with the surgical resection as the first line of treatment. Samples were first analyzed by a pathologist to macroscopically delineate the tumor, dysplasia, and peritumoral areas. The retrospective and prospective samples were sectioned into 3 consecutive sections and thaw-mounted on slides for Hematoxylin and Eosin (H&E) staining (7µm), SpiderMass analysis (20µm) and Matrix-Assisted Laser Desorption Ionization (MALDI) mass spectrometry imaging (12µm). The SpiderMass microprobe collected lipido-metabolic profiles of the tumor and peritumoral regions annotated by the pathologist. The MS spectra were then subjected to multivariate statistical analysis. The preliminary data demonstrates that the lipido-metabolic molecular profiles collected with the SpiderMass are significantly different between the tumor and peritumoral regions enabling molecular classification to be established by linear discriminant analysis (LDA). MALDI images of the different samples were submitted to segmentation for cross instrument validation and revealed additional molecular discrimination within the tumor and non-tumor regions. These very promising preliminary results show the applicability of the SpiderMass to SCC of the tongue and demonstrate its interest in the surgical treatment of head and neck cancers.